2008
DOI: 10.1002/jcb.21829
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic roles of Gab1 and Grb10 as direct cellular partners in the regulation of MAP kinase signaling

Abstract: Functions of signaling mediators Grb10 or Gab1 have been described in mitogenesis but remained disconnected. Here, we report the peptide hormone-dependent direct association between Grb10 and Gab1 and their functional connection in mitogenic signaling via MAP kinase using cultured fibroblasts as a model. In response to PDGF-, IGF-I, or insulin increased levels of Grb10 potentiated cell proliferation or survival whereas dominant-negative, domain-specific Grb10 peptide mimetics attenuated cell proliferation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Furthermore, in response to PDGF, IGF-1 and insulin, Grb10 potentiates cell proliferation [15]. This biological effect is mediated through association of Grb10 with Gab1.…”
Section: The Role Of Grb10 In Insulin Receptors Signalingmentioning
confidence: 99%
“…Furthermore, in response to PDGF, IGF-1 and insulin, Grb10 potentiates cell proliferation [15]. This biological effect is mediated through association of Grb10 with Gab1.…”
Section: The Role Of Grb10 In Insulin Receptors Signalingmentioning
confidence: 99%
“…Accordingly, overexpression of Grb10 inhibits the PI3K/AKT and MAPK pathways whereas Grb10 deficiency increases the insulin-dependent phosphorylation of proteins within these pathways, including AKT and MAPK1 (26)(27)(28)(29). Conflicting studies, however, have reported that Grb10 has a positive effect on insulin signaling (9,30). It has been proposed that these results are due to the overexpression of different Grb10 isoforms and/or the use of cell types that are not insulin-sensitive (25).…”
Section: Grb10 Is a Negative Regulator Of Growthmentioning
confidence: 99%
“…Paradoxically, stimulatory effects of Grb10 over‐expression on mitogenic effects of insulin and IGF–1 in NIH3T3 fibroblasts and on metabolic effects of insulin in L6 myoblasts and 3T3L1 adipocytes have also been reported. Whether, as previously proposed , these opposite effects reflect the use of different Grb10 isoforms and domains, cell lines that are not representative of insulin target cells, and/or non‐physiological levels of Grb10 expression remains unclear.…”
Section: Involvement Of Grb10/14 In Insulin and Igf–1 Actionmentioning
confidence: 99%